Responding to the covid-19 in West Bank Palestine refugee camps: lessons and role of community engagement - Lama Shakhshir; Weeam Hammoudeh (BMC Public Health)
Abstract Background Global unpreparedness was noted, where even high-income countries with their established healthcare systems could not cope with the Covid-19 pandemic. In the Occupied Palestinian Territory (OPT), especially in the Palestinian refugee camps, Covid-19 was an additional burden on multiple levels. Objective The aim of this study is to understand the notion of Covid-19 responses in the West Bank refugee camps and the health system’s ability to meet the needs of the refugees as well as the role of local community actors in the response. Methods Qualitative data were collected through semi-structured interviews. In total, 27 interviews were conducted with popular committees in camps, professionals working at the Palestinian Ministry of Health in addition to local and international health-related non-governmental organizations (NGOs). Participants were contacted via phone calls, Zoom meetings and in-person, for one to one and a half hours maximum. Questions were about the impact of Covid-19 and the way the participants and their organizations responded to this pandemic. Results Our findings state that wide-scale multilevel Covid-19 responses were conducted from different committees and institutions in the OPT. For example, the popular committees took part in distributing medicines, food parcels and hygiene kits, and the NGOs provided refugees with educational materials and psychosocial support. However, the overstretched Palestinian health system, the limited resources in addition to the poor coordination between health providers and poor follow up of the imposed restrictions, hindered the fast and effective response. Community engagement was a remarkable element which contributed to the successful deployment of response plans. This was demonstrated by the collaboration of the camps’ local bodies in addition to the initiatives of the local community in camps. Conclusion Covid-19 impacts were particularly pronounced for refugees where response efforts did not fulfil their needs. The study highlights the importance of preparedness, working with community organisations and designing interventions in a human-centred/community-centred way to increase the effectiveness of health interventions and responses.